MODEL PENINGKATAN KINERJA GURU SMK NEGERI 1 BAWEN - Sri Supratni; Heru Sulistyo (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2015)
Human resources is a very important factor as a driver in the face of global current era. The competitiveness of an organization depends on human resources owned. Particularly associated with either organization and organizational commitment of teacher performance. This study aims to analyze the performance of the teachers SMK Negeri I Bawen Semarang District. Variables used in this study is to use a variable of transformational leadership and work ethic of Islam. Transformational leadership and the Islamic work ethic serves as the independent variable in analyzing the performance of teachers of SMK Negeri I Bawen Semarang District. In addition to these two variables, there are still other variables used in this research thatorganizational commitment variable that serves as an intervening variable. This research usesensus method with a number of respondents as much as 78 teachers at SMK Negeri I Bawen Semarang District. Teknik of data analysis used in this study using data analysis techniques using the sruktural equation model Smart PLS (Partial Least Squere ). The results of this study indicate that transformational leadership variables and the Islamic work ethic has a positive and significant influence on organizational commitment. Variable transformational leadership, Islamic work ethic and organizational commitment showed positive and significant impact onthe performance of teachers.Keywords :Transformational leadership, Islamic work ethic, organizational Commitment and teacher performance.